Pelvic and breast ultrasound abnormalities and associated metabolic disturbances in girls with premature pubarche due to adrenarche. (27th December 2021) - Aydin, Banu K.; Kadioglu, Alev; Kaya, Gamze A.; Devecioglu, Esra; Bas, Firdevs; Poyrazoglu, Sukran; Gokcay, Gulbin; Darendeliler, Feyza
Abstract: Objective: Premature adrenarche (PA) has been suggested as a risk factor for future health problems, such as metabolic syndrome and early menarche. However, not all girls with PA have these features and it is not certain who will develop them. We propose that these abnormalities might be identified earlier, even before they are visible. Design: Case‐control study. Setting: Tertiary care hospital. Participants: Forty‐eight girls with premature pubarche due to PA and age (mean age 7.6 ± 1.0 years), weight, body mass index (BMI), birth weight and gestational age‐matched 49 girls with no palpable breast tissue. Measurements: Early pubertal pelvic and breast ultrasonographic changes and their associations with obesity and metabolic parameters were evaluated. Blood samples were collected, breast and pelvic ultrasound examinations were performed and bone ages were assessed. Results: Girls with PA were taller and their bone ages were higher ( p  = .049 and p  = .005). Fasting blood glucose, insulin, triglycerides, high‐density lipoprotein and low‐density lipoprotein cholesterol were not different between the groups. Luteinizing hormone (LH), follicle‐stimulating hormone (FSH) and estradiol were not different either. Ultrasonography revealed breast gland tissue in 30% of girls with PA and 5% of controls ( p  = .006). Uterine volume and endometrial thickness were higher in girls with PA ( p  = .03 and p  = .04). Endometrial thickness was positively associated with serum insulin levels in the whole study group and after adjusting for age, diagnosis, BMI, mean ovarian volume and LH, FSH, estradiol levels, this association remained with a borderline p ‐value ( R 2  = 0.486, p  = .050). Conclusions: We found early changes in uterus and breast glands of girls with PA and endometrial thickness was positively associated with insulin levels.